THE GROWTH RESPONS OF YELLOW PUMP PLANTS (SQUASH HYBRID F1) IN VARIOUS OF GROWING MEDIA COMPOSITION - sp, hertati; sp, maulidi; mustamir, elly (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTThe study aims to obtain the best composition of growing media for the growth of yellow pump plants plants. The research began from November 9, 2018 to January 9, 2019. The research was conducted at Jl. Purnama Agung VII, Komplek Pondok Agung Permata, Parit tokaya Village, South Pontianak. The method used was Completely Randomized Design (CRD) consisting of 5 treatments, 5 replications and for each replication there were 4 plant samples. The treatment are as follows: (m1) alluvial soil: cow manure : sand (2: 1: 1), (m2) alluvial soil: cocopeat: sand (2: 1: 1), (m3) alluvial soil: husk charcoal: sand ( 2: 1: 1), (m4) alluvial soil: cow manure: cocopeat: sand (2: ½: ½: 1) and (m5) alluvial soil: cow manure: husk charcoal: sand (2: ½: ½: 1 ) The variables observed in this study were Root Volume (cm3), Leaf Area (cm2), Fresh Weight (g) and Plant Dry Weight (g). The results shows that the composition of growing media contained cow manure provided a better for variable plant dry weight growth response compared to the composition of the growing media without cow manure. Keywords: Alluvial soil, Cocopeat , Cow manure, Growing media, Husk charcoal, Pumpkin.